Advances in Resist Technology and Processing XVII 2000
DOI: 10.1117/12.388290
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of structure profiles in optical lithography of thick DNQ-novolak-based photoresists

Abstract: DNQ-Novolak based photoresists are applied in many fields of microstructure technology. A common feature of such resist structures (>lOjim) described in the literature is a concave profile with the narrowest part at approximately 2/3 of the resist height. By newly including effects of residual solvent concentration, the simulation program accurately describes characteristic resist profiles for AZ4562 between 10 and iøøm resist thickness. The program calculates the vertical distribution of the residual solvent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Second, the influence of transport of material by convection on the dissolution rate should be verified. Simulation results may be improved by considering problems specific to thick-photoresist lithography, such as light propagation in thick photoresist [18], the influence of the solvent concentration [20], variation in photoresist properties, such as the refractive index and absorption coefficient, along the thickness direction [21], and reflection from the substrate [22]. Improvement and investigation of these points will be the subject of future work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the influence of transport of material by convection on the dissolution rate should be verified. Simulation results may be improved by considering problems specific to thick-photoresist lithography, such as light propagation in thick photoresist [18], the influence of the solvent concentration [20], variation in photoresist properties, such as the refractive index and absorption coefficient, along the thickness direction [21], and reflection from the substrate [22]. Improvement and investigation of these points will be the subject of future work.…”
Section: Discussionmentioning
confidence: 99%
“…A similar dependence is observed for prebake temperature; for a given pre-bake time, measured depth increases with decreasing pre-bake temperature (figure 4(b)). These photoresist performances are dominated by solvent content, which is varied by changing the pre-bake time and temperature [20].…”
Section: Moving Mask Uv Lithography Experimentsmentioning
confidence: 99%
“…To predict the average diluent concentration as a function of the processing parameters, a mathematical model was developed in this work. Chung et al (2000) modelled and Engelke et al (2007) experimentally showed that the residual diluent concentration is very non-uniform over the depth of a thick resist layer. This is because of the diffusive mechanism of molecular transportation in a very viscous prepolymer medium (up to 80,000 cSt, as notified by MicroChem (2007)).…”
Section: Diluent Diffusion Modelmentioning
confidence: 98%
“…These reports include the characterization of the DNQ photoresist property [33][34][35][36][37], photolithography simulation models [38][39][40][41][42][43][44][45][46][47][48], and so on. In the past few years, a growing number of research groups reported the DNQ photoresist as a thick photoresist for MEMS applications [49][50][51][52][53][54][55][56][57][58][59]. However, compared to the previously reported studies of the DNQ photoresist with thickness of less than 25 μm, the number of publications on 3D thick-photoresist microstructures using more than 25 μm thickness and its detail experimental study is very limited [20,60].…”
Section: Introductionmentioning
confidence: 99%